Ukhuwah Islamiyah dan Interaksi Harmonis Antarumat Beragama di Indonesia: Kajian Tafsir Ayat-Ayat Ukhuwah dalam Al-Qur’an - Shohib, Muhammad; Al Masithoh, Silvinatin; Al-Ghifari, Fahmul Hikam (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
Indonesia, with its religious, ethnic, and cultural diversity, requires a value foundation that can strengthen harmonious interfaith interactions. One relevant concept in this context is Ukhuwwah Islamiyah, or Islamic brotherhood, which teaches the importance of solidarity, tolerance, and mutual respect. This study aims to analyze the concept of Ukhuwwah Islamiyah in the Qur'an and its implications for interfaith interactions in Indonesia. The method used in this research is a descriptive qualitative approach, analyzing Qur'anic verses related to the values of brotherhood and tolerance, along with tafsir from various scholars. The findings show that the Qur'an emphasizes the importance of solidarity among human beings, not only within the Muslim community but also in relation to other religious communities. Verses such as QS. Al-Hujurat: 10 and QS. Al-Kafirun: 6 stress the principles of unity and respect for religious differences. However, challenges such as radicalization and social conflict remain obstacles to realizing true Ukhuwwah. This study contributes to understanding the relevance of the values of Ukhuwwah Islamiyah in enhancing tolerance and solidarity among religious communities in Indonesia and offers solutions to address these challenges through education and interfaith dialogue.